A high temperature aging resistant TPO waterproofing coil base material and preparation method thereof
By using modifiers such as thiol modified concave and convex rod soil and basalt fibers in the TPO waterproof roll material, a TPO waterproof roll material base that is resistant to aging and high temperature resistant is prepared, which solves the serious problem of thermal aging in the existing TPO waterproof roll material in a high temperature environment, and achieves good high-temperature aging effect and low-cost preparation.
Patent Information
- Application Number
- CN202510104139.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing TPO waterproof coils have severe thermal aging in high temperature environments and are flammable, making it difficult to take into account both the aging resistance and high temperature resistance.
A thiol-modified concave and convex rod soil and basalt fibers are used as modifiers, combined with TPO elastomers, antioxidants and fillers, and aging-resistant and high-temperature-resistant TPO waterproof coil base material is prepared by mixing the mixer.
The TPO waterproof coil still maintains tensile strength of more than 90% at high temperature of 135°C for 56 days, and the preparation method is simple and the manufacturing cost is low.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TPO waterproof coiled materials, in particular to a high temperature aging resistant TPO waterproof coiled material base material and a preparation method thereof. Background Art
[0002] Thermoplastic polyolefin (TPO) waterproofing membrane is a new type of waterproofing membrane made of an elastomeric material composed of two components, rubber and polyolefin, and is blended with modifiers and masterbatches as needed. It has excellent impermeability, frost resistance, elasticity and fatigue resistance, and is suitable for single-layer roofs, planted roofs and underground waterproofing projects. However, TPO materials are flammable materials with low ignition points and severe thermal aging under high temperature environments. To solve this problem, the conventional practice is to add antioxidants to prevent thermal oxidative degradation of polymer materials. In addition, Chinese patent CN116102804A also discloses that the use of thermoplastic rubber SEBS and TPU can improve the thermal aging performance of TPO waterproofing membranes; Chinese patent CN114805974A discloses that the weather resistance of waterproofing membranes can be improved by adding talcum powder, a material with good thermal stability, and improving the compatibility between talcum powder and matrix resin. It can be seen that in order to solve the problem of TPO's poor heat resistance and high temperature resistance, researchers have proposed different solutions. How to obtain a low-cost, high-performance, aging-resistant and high-temperature-resistant TPO waterproof membrane is currently a hot topic of research.
[0003] Attapulgite, also known as palygorskite, is a hydrous magnesium-rich silicate clay mineral with a chain-layered structure. It has the characteristics of loose and porous structure, large specific surface area, and good heat resistance. These characteristics make attapulgite widely used in the modification of polymer compounds. For example, Xu Guoyong, Wang Pinghua and others pointed out that the application of attapulgite in the polymer field involves the plastic industry, rubber industry, coating industry, leather and building materials industry, etc. Among them, in the coating industry, because attapulgite has certain colloidal suspension and adsorption capabilities, it can be used as a filler, thickener, leveling agent and stabilizer for architectural coatings and waterproof coatings. Wu Guohua and others pointed out that attapulgite can greatly improve the rheological properties of coatings. However, the current application basically stays in the direct application of attapulgite, and there is little research on the performance and application of modified attapulgite. The surface of attapulgite is rich in polar Si-OH groups, so it can be treated with a coupling agent. Using different coupling agents will result in modified attapulgite with different properties. How to apply modified attapulgite to the field of waterproof membranes to prepare a polymer waterproof coating is a problem that needs to be solved urgently, and it is also the key to the industrialization of attapulgite application.
[0004] The present invention aims to provide a novel TPO waterproofing coil base material by using attapulgite as a raw material, so that the base material can have good aging resistance and high temperature resistance effects at a lower manufacturing cost. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a high temperature aging resistant TPO waterproofing membrane base material and a preparation method thereof, so as to at least achieve a higher high temperature aging resistance effect.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] The base material of the aging-resistant and high-temperature-resistant TPO waterproofing membrane includes the following raw materials: mercapto-modified attapulgite, TPO elastomer, antioxidant, basalt fiber and filler.
[0008] Furthermore, the raw materials include, by weight:
[0009] 4-5 parts of mercapto-modified attapulgite, 80-90 parts of TPO elastomer, 0.05-0.1 parts of antioxidant, 3-4 parts of basalt fiber and 3-4 parts of filler.
[0010] Furthermore, the filler includes titanium dioxide or magnesium hydroxide.
[0011] Furthermore, the antioxidant is preferably pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxyhydrocinnamate), CAS: 6683-19-8.
[0012] Furthermore, the raw materials may be added with light stabilizers, flame retardants and masterbatches as required.
[0013] Another object of the present invention is to provide a method for preparing the TPO waterproofing membrane base material, comprising the following steps:
[0014] S1: mixing attapulgite and a thiol modifier, stirring at room temperature, and then washing and drying to obtain the thiol-modified attapulgite;
[0015] S2: Mixing the TPO elastomer, basalt fiber, mercapto-modified attapulgite, antioxidant and filler in an internal mixer to obtain the TPO waterproofing membrane base material.
[0016] Furthermore, in step S1, the mercapto modifier is a 5% 3-mercaptopropyltrimethoxysilane ethanol solution.
[0017] Furthermore, in step S1, the solid-liquid ratio of the attapulgite to the thiol modifier is 1:8-10.
[0018] Furthermore, in step S2, the mixing temperature is 180-200° C.; and / or the mixing time is 5-8 min.
[0019] Furthermore, in step S2, the stirring speed of the mixing is 50-60 r / min.
[0020] Another object of the present invention is to provide an application of the TPO waterproofing membrane base material in preparing a TPO waterproofing membrane, comprising the following steps:
[0021] The TPO waterproofing coiled material base material is subjected to sheeting or extrusion granulation.
[0022] The beneficial effects of the present invention are:
[0023] The present invention adopts mercapto-modified attapulgite and basalt fiber as modifiers to prepare an aging-resistant and high-temperature resistant TPO waterproof coil base material. With the addition of less antioxidant, it has a better high-temperature aging resistance effect. After heat aging at a high temperature of 135°C for 56 days, it still maintains more than 90% of the tensile strength. The preparation method is simple and the manufacturing cost is low. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described in detail below, but the protection scope of the present invention is not limited to the following.
[0025] Sources of reagents used in the following examples:
[0026] Attapulgite: purchased from Hongzhi Mineral Products Factory, Mingguang City, Anhui Province. 3-Mercaptopropyltrimethoxysilane ethanol (KH-590): purchased from Guangzhou Jianshuang Chemical Technology Co., Ltd. Basalt fiber, purchased from Tai'an Anfeng New Material Technology Co., Ltd. Antioxidant 1010: purchased from Merck. TPO elastomer: brand F-3710 / Pureman, purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd., performance parameters: melt index: 4.5g / 10 min, tensile strength: 17.5MP, a flexural modulus: 220MPa, flexural strength: 10.5MPa.
[0027] Example 1
[0028] A method for preparing an aging-resistant and high-temperature-resistant TPO waterproofing membrane base material and a TPO waterproofing membrane is as follows:
[0029] 1) Put dry attapulgite into a beaker, and then take 5% 3-mercaptopropyltrimethoxysilane ethanol solution (obtained by diluting 20% 3-mercaptopropyltrimethoxysilane ethanol solution four times with distilled water), with a solid-liquid ratio of 1g:10mL, and then transfer the mixed solution into the beaker with attapulgite, mix well, stir at room temperature for 6 h on a magnetic stirrer, let stand, wash with water until neutral, place in an oven at 80°C to dry, grind to 200 mesh and place in a desiccator for use, to obtain thiolated attapulgite.
[0030] 2) Add 900g TPO elastomer, 40g basalt fiber, 40g thiolated attapulgite, 1g antioxidant 1010 and 30g titanium dioxide into an internal mixer, set the mixer speed to 50r / min, set the temperature to 180°C, and react for 8min to obtain the TPO waterproof membrane base material.
[0031] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0032] Example 2
[0033] A method for preparing an aging-resistant and high-temperature-resistant TPO waterproofing membrane base material and a TPO waterproofing membrane is as follows:
[0034] 1) Put dry attapulgite into a beaker, and then take 5% 3-mercaptopropyltrimethoxysilane ethanol solution (obtained by diluting 20% 3-mercaptopropyltrimethoxysilane ethanol solution four times with distilled water), with a solid-liquid ratio of 1g:10mL, and then transfer the mixed solution into the beaker with attapulgite, mix well, stir at room temperature for 6 h on a magnetic stirrer, let stand, wash with water until neutral, place in an oven at 80°C to dry, grind to 200 mesh and place in a desiccator for use, to obtain thiolated attapulgite.
[0035] 2) Add 850g of TPO elastomer, 40g of basalt fiber, 50g of thiolated attapulgite, 0.5g of antioxidant 1010 and 35g of titanium dioxide into an internal mixer, set the speed of the internal mixer to 60r / min, set the temperature to 190°C, and react for 6min to obtain the TPO waterproof membrane base material.
[0036] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0037] Example 3
[0038] A method for preparing an aging-resistant and high-temperature-resistant TPO waterproofing membrane base material and a TPO waterproofing membrane is as follows:
[0039] 1) Put dry attapulgite into a beaker, and then take 5% 3-mercaptopropyltrimethoxysilane ethanol solution (obtained by diluting 20% 3-mercaptopropyltrimethoxysilane ethanol solution four times with distilled water), with a solid-liquid ratio of 1g:10mL, and then transfer the mixed solution into the beaker with attapulgite, mix well, stir at room temperature for 6 h on a magnetic stirrer, let stand, wash with water until neutral, place in an oven at 80°C to dry, grind to 200 mesh and place in a desiccator for use, to obtain thiolated attapulgite.
[0040] 2) Add 800g of TPO elastomer, 30g of basalt fiber, 45g of thiolated attapulgite, 0.8g of antioxidant 1010 and 40g of titanium dioxide into an internal mixer, set the speed of the internal mixer to 50r / min, set the temperature to 200°C, and react for 5min to obtain the TPO waterproof membrane base material.
[0041] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0042] Comparative Example 1
[0043] A TPO waterproofing membrane was prepared by the same method as in Example 1, except that the attapulgite was not modified with mercapto groups, and only washed and dried attapulgite was added. The specific method is as follows:
[0044] 1) Add 900g TPO elastomer, 40g basalt fiber, 40g attapulgite, 1g antioxidant 1010 and 30g titanium dioxide into an internal mixer, set the speed of the internal mixer to 50r / min, set the temperature to 180°C, and react for 8min to obtain the TPO waterproof membrane base material.
[0045] 2) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0046] Comparative Example 2
[0047] A TPO waterproofing membrane is prepared by the same method as in Example 1, except that basalt fiber is not added. The specific method is as follows:
[0048] 1) Put dry attapulgite into a beaker, and then take 5% 3-mercaptopropyltrimethoxysilane ethanol solution (obtained by diluting 20% 3-mercaptopropyltrimethoxysilane ethanol solution four times with distilled water), with a solid-liquid ratio of 1g:10mL, and then transfer the mixed solution into the beaker with attapulgite, mix well, stir at room temperature for 6 h on a magnetic stirrer, let stand, wash with water until neutral, place in an oven at 80°C to dry, grind to 200 mesh and place in a desiccator for use, to obtain thiolated attapulgite.
[0049] 2) Add 900g of TPO elastomer, 40g of mercapto-attapulgite, 1g of antioxidant 1010 and 30g of titanium dioxide into an internal mixer, set the speed of the internal mixer to 50r / min, set the temperature to 180°C, and react for 8min to obtain the TPO waterproof membrane base material.
[0050] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0051] Comparative Example 3
[0052] An asphalt waterproof coating is prepared by the same method as in Example 1, except that the attapulgite is modified by amino. The specific method is as follows:
[0053] 1) Take dry attapulgite and put it in a beaker, then take 5% of silane coupling agent KH550, the solid-liquid ratio is 1g:10mL, then transfer the mixed solution into the beaker with attapulgite, mix well, stir on a magnetic stirrer at room temperature for 6 h, let it stand, wash with water until neutral, place it in an oven at 80℃ to dry, grind it to 200 mesh and place it in a dryer for use, to obtain amino attapulgite.
[0054] 2) Add 900g TPO elastomer, 40g basalt fiber, 40g amino attapulgite, 1g antioxidant 1010 and 30g titanium dioxide into an internal mixer, set the mixer speed to 50r / min, set the temperature to 180°C, and react for 8min to obtain the TPO waterproof membrane base material.
[0055] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0056] Comparative Example 4
[0057] An asphalt waterproof coating is prepared by the same method as in Example 1, except that no antioxidant is added. The specific method is as follows:
[0058] 1) Put dry attapulgite into a beaker, and then take 5% 3-mercaptopropyltrimethoxysilane ethanol solution (obtained by diluting 20% 3-mercaptopropyltrimethoxysilane ethanol solution four times with distilled water), with a solid-liquid ratio of 1g:10mL, and then transfer the mixed solution into the beaker with attapulgite, mix well, stir at room temperature for 6 h on a magnetic stirrer, let stand, wash with water until neutral, place in an oven at 80°C to dry, grind to 200 mesh and place in a desiccator for use, to obtain thiolated attapulgite.
[0059] 2) Add 900g of TPO elastomer, 40g of basalt fiber, 40g of thiolated attapulgite and 30g of titanium dioxide into an internal mixer, set the speed of the internal mixer to 50r / min, set the temperature to 180°C, and react for 8min to obtain the TPO waterproof membrane base material.
[0060] 3) Place the amorphous TPO waterproofing membrane base material on a tablet press while it is hot for tableting, and after natural cooling, the modified TPO waterproofing membrane is obtained.
[0061] Experimental example
[0062] The waterproof membranes of Examples 1 to 3 and Comparative Examples 1 to 4 were tested for anti-aging performance and high temperature resistance, and the specific methods are as follows:
[0063] Test pieces of 150 mm × 50 mm were taken respectively, and the tensile properties of the test pieces before and after thermal aging were tested.
[0064] The heat aging method is as follows: the test pieces are placed in an oven at 135°C for aging for 28 days and 56 days.
[0065] The tensile performance testing method is: tensile strength test according to Class H of GB 27789--2011 "Thermoplastic Polyolefin (TPO) Waterproof Membrane", tensile speed (250*50) mm / min.
[0066] The test results are as follows (tensile strength / MPa):
[0067] Before heat aging Heat aging 28d Heat aging 56 days Example 1 22.56 21.43 20.82 Example 2 22.83 21.62 20.94 Example 3 22.14 21.55 20.47 Comparative Example 1 20.43 18.54 15.63 Comparative Example 2 19.62 15.96 13.28 Comparative Example 3 22.54 19.23 17.64 Comparative Example 4 22.64 18.23 16.40
[0068] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. High temperature aging resistant TPO waterproofing membrane base material, characterized in that: Ingredients include: Mercapto-modified attapulgite, TPO elastomer, antioxidant, basalt fiber and filler; The preparation method of the TPO waterproofing coiled material base material comprises the following steps: S1: mixing attapulgite and a thiol modifier, stirring at room temperature, and then washing and drying to obtain the thiol-modified attapulgite; S2: mixing the TPO elastomer, basalt fiber, mercapto-modified attapulgite, antioxidant and filler in an internal mixer to obtain the TPO waterproofing membrane base material; By weight, the raw materials include: 4-5 parts of mercapto-modified attapulgite, 80-90 parts of TPO elastomer, 0.05-0.1 parts of antioxidant, 3-4 parts of basalt fiber and 3-4 parts of filler; The filler includes titanium dioxide or magnesium hydroxide; In step S1, the mercapto modifier is a 5% 3-mercaptopropyltrimethoxysilane ethanol solution.
2. The TPO waterproofing membrane base material according to claim 1, characterized in that: The raw materials also include light stabilizers, flame retardants and masterbatches.
3. The TPO waterproofing membrane base material according to claim 1, characterized in that: In step S1, the solid-to-liquid ratio of the attapulgite to the thiol modifier is 1 g:10 mL.
4. The TPO waterproofing membrane base material according to claim 1, characterized in that: In step S2, the mixing temperature is 180-200°C; and the mixing time is 5-8 minutes.
5. The TPO waterproofing membrane base material according to claim 1, characterized in that: In step S2, the stirring speed of the mixing is 50-60 r / min.
6. Use of the TPO waterproofing membrane base material according to any one of claims 1 to 5 in preparing TPO waterproofing membrane, characterized in that: The following steps are involved: The TPO waterproofing coiled material base material is subjected to sheeting or extrusion granulation.
Citation Information
Patent Citations
Weather-resistant TPO waterproof coiled material and preparation method thereof
CN114805974A
High-temperature-resistant TPO waterproof coiled material and preparation method thereof
CN116102804A
Long-acting waterborne nanometer attapulgite clay / epoxy anticorrosive coating material and preparing method thereof
CN102676028A
Thermoplastic elastomer material with low thermal expansion and cold contraction as well as preparation method and application of thermoplastic elastomer material
CN117534935A